Are short opercula and lower jaw deformity in Atlantic salmon Salmo salar related to triploidy? - Gianluca Amoroso; Mark Adams; Ventura, T; Christopher Carter; Battaglene, S; Elizur, A; Cobcroft, J (2014)
Short opercula and lower jaw deformity (LJD) are two skeletal anomalies commonly reported for Atlantic salmon. The first consists of a reduction or a bending of the opercular plate and the second of a downward curvature of the bones of the lower jaw (Fig. 1 and 2). Both have a negative impact on production efficiency through product downgrading, and animal welfare via higher susceptibility to diseases and mortality. The causes of the two anomalies are unknown, although triploidy is associated with a higher prevalence of LJD but not of short opercula. They may be triggered by environmental, nutritional or genetic factors in association with physiological characteristics of triploids in the case of LJD. In order to describe the ontogeny of opercular and jaw skeletal structures and to understand molecular mechanisms underlying the onset of short opercula and LJD, diploid and triploid (produced by pressure shock) Atlantic salmon embryos, from the same pooled batch of fertilised eggs (6 females and 2 males), were collected from a commercial hatchery. The embryos were incubated, and alevins and parr were reared for 9 months in the Aquaculture Centre at the University of Tasmania (Launceston) to compare early development. Diploid and triploid individuals were held separately, under the same environmental conditions: temperature 7.8 ± 0.2˚C (mean ± SD), DO 98.9 ± 1.1%, pH 7.2 ± 0.3, NH3 0.12 ± 0.12 ppm, NO2 0.01 ± 0.05 ppm, NO3 1.5 ± 2.3 ppm during the incubation period and temperature 13.6 ± 1.2˚C , DO 96.1 ± 2.2%, pH 7.0 ± 0.2, NH3 0.05 ± 0.10 ppm, NO2 0.02 ± 0.07 ppm, NO3 7.6 ± 4.3 ppm during the swim-up to parr stage. The fish were fed commercial diets. Embryos were sampled weekly until first feeding, then monthly until the end of the experiment. At 1973 ˚days (cumulative average daily temperature), there was no significant difference in size of diploids and triploids which were 3.15 ± 0.13 g and 64.8 ± 0.8 mm (FL), and 2.92 ± 0.18 g and 63.8 ± 1.1 mm (FL), respectively. A very high prevalence of short opercula ...